Building urban lives: female migrant workers emotional counter-topographies in China - Jayne, Mark; Siying, Wu; Chenhui, Wu (Eurasian geography and economics, 2025)
This paper develops new ontological and epistemological terrain to advance critical understanding of migrants' everyday lives in urban china. More specifically, we highlight the opportunities afforded by pluralist relational theoretical and comparative empirical interrogation of emotions across diverse work, domestic, family and leisure times/spaces both within and, beyond cities. To that end, we apply a counter-topographical approach to a kaleidoscope of imaginative, implosive, and mutual emotions as competences and resources that constitute past, present, and future lives of female building-workers. Concluding, we signpost fruitful avenues for ongoing migration research in China, as well as reflecting on broader opportunities and challenges when exploring the complex emotional lives of urbanites no matter where in the world studies are undertaken.